2012
DOI: 10.1371/journal.pone.0035434
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Host-Range of the Rust Fungus Puccinia psidii sensu lato across Tribes of the Family Myrtaceae Present in Australia

Abstract: The exotic rust fungus Puccinia psidii sensu lato was first detected in Australia in April 2010. This study aimed to determine the host-range potential of this accession of the rust by testing its pathogenicity on plants of 122 taxa, representative of the 15 tribes of the subfamily Myrtoideae in the family Myrtaceae. Each taxon was tested in two separate trials (unless indicated otherwise) that comprised up to five replicates per taxon and six replicates of a positive control (Syzygium jambos). No visible symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 29 publications
2
89
0
3
Order By: Relevance
“…This suggests that it may have the potential to infect many other hosts in the sub-family Myrtoideae, including commercially important eucalypts and P. guajava. Morin et al (2012), conducted extensive host range studies of Australian Myrtaceae and concluded that there is no apparent association between the presence or absence of P.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that it may have the potential to infect many other hosts in the sub-family Myrtoideae, including commercially important eucalypts and P. guajava. Morin et al (2012), conducted extensive host range studies of Australian Myrtaceae and concluded that there is no apparent association between the presence or absence of P.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its halophilic nature it is usually found on sandy soils. This species has been tested and found to be susceptible to A. psidii, showing high variability within the species ranging from resistant individuals to very susceptible ones (Morin et al 2012). Shoots can be infected as well as leaves and a reduction in flower production has been observed as a result of repeated infection (Dr G. Pegg 2015, pers.…”
Section: Study Speciesmentioning
confidence: 99%
“…However, there remain significant challenges such as maintaining yields in resistant material. Under particular threat is the tea tree oil industry because Melaleuca alternifolia shows high levels of susceptibility to the rust (Morin et al 2012). Although the full effect of myrtle rust infection is not yet known, it has the potential to cause enormous losses.…”
Section: Overview and Conclusionmentioning
confidence: 99%